Transitional care models in adolescent kidney transplant recipients—a systematic review. Issue 1 (12th May 2022) - Wildes, Dermot Michael; Costigan, Caoimhe S; Kinlough, Mairead; Flynn, Joan; Dolan, Niamh; Riordan, Michael; Sweeney, Clodagh; Stack, Maria; Waldron, Mary; Walsh, Orla; Gorman, Kathleen M; Awan, Atif
ABSTRACT: Background: Adolescence is a time of significant change for patients, guardians and clinicians. The paediatrician must ensure patients develop the necessary skills and knowledge required to transition and to function as an independent entity, with autonomy over their own care. The transfer from paediatric to adult care carries an increased risk of graft-related complications attributable to a multitude of reasons, particularly non-adherence to immunosuppressive medicines and poor attendance at scheduled appointments. This systematic review was conducted to ascertain the transitional care models available to clinicians caring for kidney transplant recipients and to compare the approach in each respective case. Methods: A systematic review was performed, in a methodology outlined by the PRISMA guidelines. OVID MEDLINE and EMBASE databases were searched for studies that outlined valid, replicable models pertaining to transitional care of paediatric kidney transplant recipients between 1946 and Quarter 3 of 2021. The reference lists of selected articles were also perused for further eligible studies and experts in the field were consulted for further eligible articles. Two investigators assessed all studies for eligibility and independently performed data extraction. Any discrepancies were settled by consensus. Results: A total of 1121 abstracts were identified, which was reduced to 1029 upon removal of duplicates. A total of 51 articles were deemed appropriate for full-text review and critical appraisal. A total of 12 articles that described models for transition pertaining to kidney transplant patients were included in qualitative synthesis. Every paper utilized a different transition model. All but one model included a physician and nurse at minimum in the transition process. The involvement of adult nephrologists, medical social work, psychology and psychiatry was variable. The mean age for the initiation of transition was 13.4 years (range: 10–17.5 years). The mean age at transfer to adult services was 18.3 years (range: 16–20.5 years). Conclusions: Despite the well-established need for good transitional care for paediatric solid-organ transplant recipients, models tailored specifically for kidney transplant recipients are lacking. Further research and validation studies are required to ascertain the best method of providing effective transitional care to these patients. Transitional care should become a standardized process for adolescents and young adults with kidney transplants.